New Species of Heliotropium muricatum (Boraginaceae) Indemic from Iraq. - Abbas, Yass K. (University of Thi-Qar Journal of Science, 2019)
A new endemic species . Helitropium muricatum Abbas Sp. Nov is deseribed from Iraq